2020
DOI: 10.1016/j.celrep.2020.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Gut Dysbiosis during Influenza Contributes to Pulmonary Pneumococcal Superinfection through Altered Short-Chain Fatty Acid Production

Abstract: Highlights d Influenza alters the production of SCFAs by the gut microbiota d The dysbiotic microbiota transfers susceptibility to respiratory bacterial infection d Supplementation with acetate restores the killing activity of alveolar macrophages d Activation of the SCFA receptor FFAR2 protects against bacterial superinfection

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
274
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 252 publications
(310 citation statements)
references
References 69 publications
(131 reference statements)
15
274
0
3
Order By: Relevance
“…In that context of GI Covid-19, it is expected that gut microbiota could be modified and that this could worsen the Covid-19 lung damage. Indeed, rapid and severe changes in the gut microbiota [39], a decrease in gut barrier function and increased intestinal permeability [40] could promote changes in the lung microbiota and worsen lung damage [41] leading to ARDS [42]. Conversely, the protective effect induced by a modification of the intestinal microbiota during a viral infection such as the influenza involved a stimulation of the innate immune response [43].…”
Section: Expected Benefits Of Nutrition Support In the Covid-19 Patientsmentioning
confidence: 99%
“…In that context of GI Covid-19, it is expected that gut microbiota could be modified and that this could worsen the Covid-19 lung damage. Indeed, rapid and severe changes in the gut microbiota [39], a decrease in gut barrier function and increased intestinal permeability [40] could promote changes in the lung microbiota and worsen lung damage [41] leading to ARDS [42]. Conversely, the protective effect induced by a modification of the intestinal microbiota during a viral infection such as the influenza involved a stimulation of the innate immune response [43].…”
Section: Expected Benefits Of Nutrition Support In the Covid-19 Patientsmentioning
confidence: 99%
“…Several genes in Fatty-acid synthesis pathways were down-regulated in RSV-ARI ( Figure 5d); interestingly, it has been shown that short-chain fatty acids (SCFA), speci cally acetate, have anti-viral activity against RSV 54 and in uenza A virus 55,56 . Further, microbiota-derived acetate has been shown to protect against RSV infection through a GPR43-type 1 interferon response 55 .…”
Section: Discussionmentioning
confidence: 99%
“…Several genes in Fatty-acid synthesis pathways were down-regulated in RSV-ARI ( Figure 5d); interestingly, it has been shown that short-chain fatty acids (SCFA), speci cally acetate, have anti-viral activity against RSV 54 and in uenza A virus 55,56 . Further, microbiota-derived acetate has been shown to protect against RSV infection through a GPR43-type 1 interferon response 55 . The most signi cant increase in gene expression was of ACOD1; ACOD1 is also called IRG1 and the long non-coding RNA of ACOD1 is involved in the inhibition of the in ammatory response 57 , and also serves as a negative regulator of the Toll-like receptors (TLRs)-mediated in ammatory innate response by stimulating the tumor necrosis factor alphainduced protein TNFAIP3 expression via reactive oxygen species (ROS) in LPS-tolerized macrophages 58 .…”
Section: Discussionmentioning
confidence: 99%
“…Severe influenza A virus infection is associated with intestinal disorders and gut microbiota alterations (Wang et al, 2014;Qin et al, 2015;Deriu et al, 2016;Groves et al, 2018;Yildiz et al, 2018;Sencio et al, 2020). These changes were attributed partly to infection-related reduction in food consumption (Sencio et al, 2020) and to interferon production (Wang et al, 2014;Deriu et al, 2016). We recently looked at whether microbiota conditioned by influenza A virus enhanced susceptibility to bacterial superinfection, a major cause of mortality during epidemics and pandemics (McCullers, 2014).…”
Section: The Potential Role Of the Gut Microbiota In Covid-19mentioning
confidence: 99%
“…In fecal transfer experiments, we showed that the dysbiotic microbiota remotely compromises the lung's defenses against pneumococcal infection. In mechanistic terms, a reduction in SCFA production is associated with a decrease in the alveolar macrophages' bactericidal activity (Sencio et al, 2020).…”
Section: The Potential Role Of the Gut Microbiota In Covid-19mentioning
confidence: 99%